The Second Phase of the Hall of Mirrors: the Writing Desks and the Firedogs Ordered by Velazquez to Italy (1649-1660) - Cruz Yábar, Juan María (Anales de Historia del Arte, 2017)
We are reviewing the decoration commissioned by Velazquez to Italy bound for the Hall of Mirrors in the Alcazar in the decade of 1650, and we reveal how the famous lions were conceived with cornucopias on the heads to be used as torch stands before he had to adapt them as table supports. Being in Madrid, the arrival of some porphyry vases caused that they ordered table-tops of this material for the writing-desks. The changing role of the lions made way in the fireplaces for firedogs of the four Elements requested duplicate to Algardi, an order which circumstances we clarify as its style and iconography, and we demonstrate that another similar firedogs set was made being still the Sevillian alive. Examinamos la decoración encargada por Velázquez a Italia con destino al Salón de los Espejos del Alcázar en la década de 1650 y desvelamos cómo los famosos leones fueron ideados con cornucopias sobre las cabezas para que sirvieran de hacheros antes de tener que adaptarlos como pies para las mesas. Estando ya en Madrid, la llegada de unos vasos de pórfido provocó que se pidieran tableros de esta materia para los bufetes. El cambio de función de los leones dejó espacio en las chimeneas para morillos de los cuatro Elementos solicitados a Algardi por duplicado, un encargo cuyas circunstancias aclaramos, así como su estilo e iconografía, y demostramos que se hizo otro juego de morillos similar aún en vida del sevillano.